2005
DOI: 10.1097/00000542-200507000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Epidural Electrical Stimulation against Ischemic Spinal Cord Injury in Rats

Abstract: Although the optimal setting for this electrical preconditioning should be determined in future studies, the results suggest that epidural electrical stimulation will be a useful approach to provide spinal protection against ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Moreover, a study of traumatic spinal cord injury by Fujiki and colleagues showed that spinal cord electrical stimulation preconditioning could attenuate progressive necrosis and cavitation, thus induced tolerance to traumatic spinal cord injury in a rat model. Furthermore, a study by Kakinohana et al showed that a single epidural electrical stimulation for 10 sec, 24 hours before spinal cord ischemia induced significant ischemic tolerance against spinal cord ischemia and the P50 (spinal cord ischemia duration with 50% probability of paraplegia) was prolonged by approximately 15% compared to the control group. Until now, studies of epidural electrical stimulation combating apoptosis all focus on SCS preconditioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a study of traumatic spinal cord injury by Fujiki and colleagues showed that spinal cord electrical stimulation preconditioning could attenuate progressive necrosis and cavitation, thus induced tolerance to traumatic spinal cord injury in a rat model. Furthermore, a study by Kakinohana et al showed that a single epidural electrical stimulation for 10 sec, 24 hours before spinal cord ischemia induced significant ischemic tolerance against spinal cord ischemia and the P50 (spinal cord ischemia duration with 50% probability of paraplegia) was prolonged by approximately 15% compared to the control group. Until now, studies of epidural electrical stimulation combating apoptosis all focus on SCS preconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while a number of studies have confirmed the existence of motor neuron apoptosis and caspase3 activation following spinal cord ischemia/reperfusion, SCS was found to inhibit apoptosis of cardiomyocytes and suppress caspase‐3 activation in research of cardiac IRI . The above research suggests that SCS may have neuroprotective effects against spinal cord IRI and previous research has shown that SCS preconditioning prolonged ischemic tolerance of the spinal cord . However, to the best of our knowledge there is no data yet available regarding the effects of SCS postconditioning on spinal cord IRI.…”
Section: Introductionmentioning
confidence: 95%
“…S pinal cord ischemia, which could result in paraplegia and paralysis, remains a devastating complication after repairing of thoracoabdominal aortic aneurysms. A variety of preconditioning stimuli have been used to render spinal cord protection, such as brief periods of ischemia (Abraham et al, 2000), transient episodes of electroconvulsion (Kakinohana et al, 2005), and exposure to anesthetic inhalants (Park et al, 2005). However, the utility of the preconditioning effects induced by these stimuli in clinical practice is questionable because of potential risks for patients.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a safe and effective neuroprotection preconditioned method is needed before surgery in clinical medical practice. Brief periods of ischemia, 28 transient episodes of electroconvulsion, 29 and exposure to anesthetic inhalants 30 has been reported to render spinal cord protection. But the application of these preconditioning stimuli in clinical setting is problematic because of potential dangers.…”
Section: Discussionmentioning
confidence: 99%